In Vitro Activity Comparison of Ceftazidime–Avibactam and Aztreonam–Avibactam Against Bloodstream Infections With Carbapenem-Resistant Organisms in China - Yu, Wei; Xiong, Luying; Luo, Qixia; Chen, Yunbo; Ji, Jinru; Ying, Chaoqun; Liu, Zhiying; Xiao, Yonghong (Frontiers in Cellular and Infection Microbiology, 2021)
Objectives The aim of this work was to investigate the activity of ceftazidime–avibactam (CZA) and aztreonam–avibactam (AZA) against bloodstream infections caused by carbapenem-resistant organisms (CROs). Methods Non-duplicate CROs, including 56 carbapenem-resistant Escherichia coli (CR-Eco), 318 carbapenem-resistant Klebsiella pneumoniae (CR-Kpn), and 65 carbapenem-resistant Pseudomonas aeruginosa (CR-Pae), were collected using the Blood Bacterial Resistant Investigation Collaborative System (BRICS) program in China. The minimum inhibitory concentrations (MICs) of 24 antibiotics were tested. Carbapenemase genes were amplified for CZA-resistant CROs by PCR. The MICs of CZA and AZA were further determined with avibactam at 8 and 16 mg/L, respectively. Results The resistance rate of polymyxin B against CROs was less than 5%. Only one CR-Kpn was resistant to tigecycline. The resistance rates of CZA against CR-Eco, CR-Kpn, and CR-Pae were 75.0%, 12.6%, and 18.5%, respectively. The MIC90 values of AZA against CR-Eco, CR-Kpn, and CR-Pae were 2/4, 1/4, and 64/4 mg/L, respectively. Among the CZA-resistant CROs, 42 (100%) CR-Eco, 24 (60%) CR-Kpn, and 1 (8.3%) CR-Pae isolates harbored metallo-β-lactamase genes. The increase of avibactam concentration enhanced the susceptibility of CZA and AZA against CROs, especially for CR-Eco and CR-Kpn. Conclusions The in vitro activity of AZA was superior to that of CZA against CR-Eco and CR-Kpn, whereas CZA showed better effect against CR-Pae.